Elastic beams and frames - Renton, J. D. 1935- (Woodhead Publishing, 2002)
The book approaches the basic theory of structures from a different perspective from standard pedagogy. There is consideration of work and energy concepts as fundamental and the equations of statics derived from them. Likewise, these concepts, together with that of the characteristic response, are used in the derivation of beam theory. Plane sections remaining plane is then seen as a particular result for isotropic, homogeneous, prismatic beams. The general theory may still be used where none of these conditions holds, and can even be applied to trusses. It also corrects errors in the theory of beam shear. Special topics discussed include non-uniform torsion, the exact analysis of shear, anisotropy, advanced energy methods, optimum structures, and regular frames. Software provided in the book includes seven general purpose programs for analysis of plane, space frames with rigid or pinned joints, and uses the augmented Gaussian elimination process and dynamic storage techniques. Approaches the basic theory of elastic beams and frames from a different perspective from standard pedagogyProvides an introduction to more advanced ideas on the theory of structures and contains much additional materialIncludes consideration of work and energy concepts as fundamental and the equations of statistics derived from them.
Keywords: Girders.; Elasticity.; Structural frames.; elektronické knihy; electronic books